The Тurkey's policy in the western balkans at the beginning of the XXI century: main directions and results - I. V. Kryuchkov (Современная наука и инновации, 2023)
The article deals with the main trends and contradictions in the development of Turkey's cooperation with the states of the Western Balkans at the beginning of the 21st century. The material highlights the reasons for the activation of Ankara's policy in the Western Balkans, its stages and mechanisms for the implementation of the set foreign policy goals. In conclusion, the author comes to the conclusion that Turkey, together with the European Union, the United States and China, is becoming the main actor in international relations influencing the development of the Western Balkans.